Enhanced Xe/Kr separation via the pore size confinement effect of a microporous thorium-based metal–organic framework. Issue 40 (3rd October 2022) - Mi, Pinhong; Chen, Lixi; Li, Xiaoqi; Wang, Xia; Li, Guodong; Cheng, Liwei; Lu, Junhao; Zhang, Hailong; Wang, Yanlong; Wang, Shuao
Abstract : A thorium-based metal–organic framework with a suitable pore size for the uptake of Xe over Kr was developed for efficient Xe/Kr separation. Abstract : A three-dimensional microporous thorium-based metal–organic framework (Th-BPYDC-I) that features a suitable pore size for Xe was prepared. The pore confinement effect enables high Xe uptake (2.15 mmol g −1 ) and good Xe/Kr selectivity (7.49). This work highlights the critical role of the size-matching rule in noble gas separation and provides an alternative option for Xe/Kr separation.